2012
DOI: 10.1117/1.jbo.17.1.017005
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic field enriched surface enhanced resonance Raman spectroscopy for early malaria diagnosis

Abstract: Hemozoin is a by-product of malaria infection in erythrocytes, which has been explored as a biomarker for early malaria diagnosis. We report magnetic field-enriched surface-enhanced resonance Raman spectroscopy (SERRS) of β-hematin crystals, which are the equivalent of hemozoin biocrystals in spectroscopic features, by using magnetic nanoparticles with iron oxide core and silver shell (Fe(3)O(4)@Ag). The external magnetic field enriches β-hematin crystals and enhances the binding between β-hematin crystals and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
79
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(79 citation statements)
references
References 39 publications
0
79
0
Order By: Relevance
“…As a successful example, the magnetic nanoparticles with iron oxide core and silver shell have been demonstrated for the efficient and early diagnosis of malaria, an infectious disease. 53 These magnetic nanoparticles showed an ability to detect β-hematin crystals, an equivalent of hemozoin biocrystals, through the magnetic field-enriched surface-enhanced resonance Raman spectroscopy. The hemozoin has been recognized as a biomarker for malaria infection, and could be used for early diagnosis of malaria.…”
Section: Application Of Nanodiagnostics In Pocts For Infectious Diseasesmentioning
confidence: 99%
“…As a successful example, the magnetic nanoparticles with iron oxide core and silver shell have been demonstrated for the efficient and early diagnosis of malaria, an infectious disease. 53 These magnetic nanoparticles showed an ability to detect β-hematin crystals, an equivalent of hemozoin biocrystals, through the magnetic field-enriched surface-enhanced resonance Raman spectroscopy. The hemozoin has been recognized as a biomarker for malaria infection, and could be used for early diagnosis of malaria.…”
Section: Application Of Nanodiagnostics In Pocts For Infectious Diseasesmentioning
confidence: 99%
“…A number of recent studies have reported on strategies to exploit physical and/or electromagnetic features of hemozoin crystals to detect infection by malaria parasites [54,[80][81][82][83][84][85][86]. Generally, the LOD of these methods is between 1 and 30 iRBCs/ml and, therefore, not as sensitive as NAA strategies.…”
Section: Emerging Malaria Diagnosticsmentioning
confidence: 99%
“…A holographic grating (1800 gr/mm) dispersed the signal into a Rem Cam CCD detector (inVia, Renishaw, Gloucestershire, UK) for analysis. The spectral resolution was 2 cm -1 and integration time was 10 s. These raw data underwent the baseline correction, followed by averaging over a five-point window to reduce noise and removal [13] of fluorescence background, which yielded the final spectra shown in the Results section.…”
Section: Raman Instrumentationmentioning
confidence: 99%
“…These spectra were averaged from five different locations with a signal standard deviation of less than 5%. Prominent Raman peaks located at about 615, 775, 1185, 1310, 1365, and 1508 cm -1 , which can be attributed to the C-C-C ring in-plane bending, CH out-of-plane bending, C-O-C stretching, C-C/C-N stretching and aromatic C-C stretching, respectively [13,18], are observed in the R6G Raman spectra measured using the microneedle based SERS probe [ Figure 2(a) and (b)]. In contrast, the ordinary Raman spectra of R6G at higher concentrations show only weak Raman peaks even at a higher excitation power of 100 mW.…”
Section: Discrete-dipole Approximation Modellingmentioning
confidence: 99%